Numerical study of cracking a medium elastic viscoplastique of polyacetal - Reffas, Sid Ahmed; Benguidiab, Mohamed; Sikula, Ondrej; Adjlout, Houari; Lebbal, Habib (Mechanics and Mechanical Engineering, 2019)
The objective of this work is the analysis of the fracture behavior of a cylinder with a defect where stress triaxiality is more severe. Numerical simulations are carried out in a 2D mode, to overcome a disadvantageous hypothesis plane strain or plane stress. The mesh sensitivity studies were also undertaken but are not presented here. Indeed, only the results for the most relevant mesh are the subject of the discussion.